DNA Repair Genes and Chronic Myeloid Leukemia: XPD (751), XRCC1 (399), XRCC4-Intron 3, XRCC4 (1394) Gene Polymorphisms - Istemi SERIN; Mustafa PEHLIVAN; Kursat OZDILLI; Fatma OGUZ SAVRAN; Gaye TOMATIR; Sacide PEHLIVAN (Mediterranean Journal of Hematology and Infectious Diseases)
No Abstract required